Rentenpaket: Die Bundesregierung auf Irrwegen - Lars P. Feld; Anabell Kohlmeier; Christoph M. Schmidt (Wirtschaftsdienst, 2014)
Das Gesetz über Leistungsverbesserungen in der Gesetzlichen Rentenversicherung ist am 1.7.2014 in Kraft getreten. Zu einer Reduktion der Altersarmut - wie die Aussagen im Bundestagswahlkampf 2013 vermuten ließen - trägt zumindest die abschlagsfreie Rente mit 63 nicht bei. Die Autoren aus dem Sachverständigenrat Wirtschaft bewerten die einzelnen Maßnahmen des Gesetzes differenziert und befürchten hohe Mehrausgaben, die die Zukunftsfähigkeit des Rentensystems gefährden. – – In the summer of 2014 Germany will witness the most substantial expansion of pension expenditures since the 1950s. Yet, while this reform package was motivated mainly by the dismal prospect of rising old age poverty rates, it does little to alleviate this problem. On the contrary, its two central elements, an expansion of the pension claims of mothers whose children were born before 1992, and access to early retirement at age 63 for workers with a long insurance history, tend to benefi t rather privileged groups of the insured. These measures endanger the sustainability of the German pension system and will necessitate future generations to work even longer than would have been the case otherwise.
Keywords: H55; J18; J26; 330; Rentenreform; Rentenfinanzierung; Nachhaltigkeit; Generationengerechtigkeit; Altersarmut; Deutschland